ZnO catalyzed transesterification of Madhuca indica oil in supercritical methanol. (15th April 2019) - Lamba, Neha; Gupta, Rimzhim; Modak, Jayant M.; Madras, Giridhar
Graphical abstract: Highlights: Transesterification of mahua oil was catalysed in supercritical methanol with ZnO. Effect of fuel in combustion synthesis and morphology of ZnO was studied. ZnO obtained by ascorbic acid as fuel in combustion synthesis showed high activity. ZnO-Nanorods showed highest activity for the transesterification reaction. Rate constants, activation energies obtained were compared with uncatalyzed reaction. Abstract: An integrated pathway (heterogeneous catalyst with supercritical pathway) was studied to develop a most viable route for the synthesis of fatty acid methyl esters useful as biodiesel. Madhuca indica (Mahua) oil was transesterified using supercritical methanol and ZnO at 523 K, 10 MPa and molar ratio of 40:1 (alcohol:oil). ZnO was synthesized by solution combustion using various fuels (urea, glycine, lactose, oxalyl dihydrazide, ascorbic acid (AA)). Also, different morphologies of ZnO (nanorods (NR), nanoflowers, nanoparticles, nanospheres) were obtained via hydrothermal, precipitation, sonochemical and sol-gel synthesis. Pseudo first order rate constants ranging from (3.46 to 16.7) × 10 −4  s −1 (>0.99 × 10 −4  s −1 for uncatalyzed reaction) at 523 K, 10 MPa were obtained. ZnO-AA (solution combustion) and ZnO-NR (hydrothermal) were found to be the most active catalysts. Activation energies of 42 kJ/mol and 17 kJ/mol (<75 kJ/mol for uncatalyzed reaction) were obtained with ZnO-AA and ZnO-NR indicating the superiority of the integrated process.